2020
DOI: 10.31557/apjcp.2020.21.8.2469
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Fucoidan Via Apoptotic and Autophagic Induction on HSC-3 Oral Squamous CellCarcinoma

Abstract: Objective: Many studies suggested that fucoidan has anticancer potential. The objective of the present study was to determine the cytotoxic effects and mechanism of cell death induced by fucoidan extracted from Fucus vesiculosus on HSC-3 oral squamous cell carcinoma. Methods: HSC-3 cells were treated with 0, 100, 200, and 400 μg/mL of fucoidan. Cell viability was measured using MTT assay. Apoptosis and cell cycle were measured with a flow cytometry-based assay. Chromatin condensation and nuclear fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…These polysaccharides are used for various purposes especially in the food-processing industry, medicine, and biotechnology (Giavasis, 2014). Several previous studies suggested that fucoidan exerts the growth and proliferation inhibition in human cancer cells via apoptotic induction (Bai et al, 2020;Blaszczak et al, 2018;Chantree et al, 2020;Deepika et al, 2019;He et al, 2019;Liu et al, 2020;Narayani et al, 2019;Palanisamy et al, 2018). Moreover, some studies reported the effect of fucoidan in suppressing the invasion (Lin et al, 2017) and metastasis (Alekseyenko et al, 2007) of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…These polysaccharides are used for various purposes especially in the food-processing industry, medicine, and biotechnology (Giavasis, 2014). Several previous studies suggested that fucoidan exerts the growth and proliferation inhibition in human cancer cells via apoptotic induction (Bai et al, 2020;Blaszczak et al, 2018;Chantree et al, 2020;Deepika et al, 2019;He et al, 2019;Liu et al, 2020;Narayani et al, 2019;Palanisamy et al, 2018). Moreover, some studies reported the effect of fucoidan in suppressing the invasion (Lin et al, 2017) and metastasis (Alekseyenko et al, 2007) of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…; [4] Cerebral cortex or cerebellar lesions with a brainstem lesion diameter of > 1.5cm may be ischemic stroke caused by latent atherosclerosis of the great arteries. [5] Color ultrasound, transcranial Doppler ultrasound, or digital subtraction angiography can show the associated intracranial or extracranial artery stenosis or occlusion rate > 50%; In addition, the diagnosis of small artery stroke (symptomatic lacunar infarction) meets only one of its diagnostic criteria: typical clinical manifestations of lacunar infarction, and imaging findings showing stroke lesions <1.5cm are consistent with clinical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…With the rapid development of genetics, the genetics of stroke has gradually become a research hotspot in recent years. Studies have shown that genetic and environmental factors play an important role in the occurrence and development of stroke (4)(5)(6)(7)(8)(9). Genome-Wide Association Study (GWAS) based on single nucleotide polymorphisms (SNPs) is a powerful tool for studying complex diseases (10).…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans, natural compounds, have excellent and obvious biological activities, including antitumor (Chantree, Surarak, Sangpairoj, Aguilar, & Hitakomate, 2020; Park, Kim, Nam, Deuk Kim, & Hyun Choi, 2011), anti‐inflammatory (Li, Yang, et al, 2021), anticoagulant (Yao, Zaw, Anderson, Hinds, & Yim, 2020), antibacterial (Ashayerizadeh, Dastar, & Pourashouri, 2020), and antioxidant activities (El Rashed et al, 2021). Especially in the aspect of antitumor activity, many studies have reported the prominent effect of fucoidan, including in prostate cancers (Rui, Pan, Shao, & Xu, 2017), breast cancers (Zhang et al, 2016), liver cancers (Wu et al, 2020), colorectal cancers (Bai et al, 2020), and ovarian cancers (Liu, Yang, Peng, Li, & Zhu, 2020).…”
Section: Introductionmentioning
confidence: 99%